Analysis of Islamic Education Financing in Improving the Quality of Education - Nurul Fajrianti; Mardyawati Yunus (Takaza Innovatix Labs Ltd., 2025)
Educational financing is a strategic aspect that determines the success of Islamic education in improving the quality of education. This study aims to analyze the concept of Islamic educational financing, sources of financing, types and components of educational costs, and strategies for optimizing financing to support improving educational quality. The study uses a qualitative approach with library research. Data were obtained from books, scientific journal articles, and relevant policy documents, then analyzed using content analysis techniques through the stages of data reduction, data presentation, interpretation, and drawing conclusions. The results show that Islamic educational financing managed effectively, efficiently, transparently, and accountably makes a significant contribution to improving educational quality, particularly in developing teacher competencies, providing facilities and infrastructure, improving the quality of learning, and utilizing educational technology. In addition, diversifying financing sources through government funds, community participation, zakat, infaq, sedekah, waqf, grants, and partnerships with various parties is an important strategy in maintaining the sustainability of Islamic educational institutions. Therefore, financing of Islamic education must be viewed as a strategic investment managed based on modern management principles and sharia values ​​to realize quality, superior, and competitive education